Analisis dan Implementasi Sistem Pengelolaan SDM menggunakan Aplikasi Odoo pada Medinat Art - Sri Rejeki; Suhendi Suhendi (Jurnal Informatika Terpadu, 2020)
Medinat Art is an online-based business institution that has been established in 2015. It is slowly starting to improve its HR management to make it more structured. One of the efforts made was using the HR Information System, namely the Odoo application, to manage employee leave. The Odoo application is an Enterprise Resource Planning (ERP) application made in Open Source. Previously, Medinat Art still needed to fix many things regarding the leave management carried out. One of them is the leave application process which is still manual and unstructured because there is no official SOP. The problem that occurs is that there is no place to find out the history of employee leave, both those submitted and the remaining rights to leave, and there is a sudden impression that there is no planned delegation of tasks before the employee leaves. The module applied in this research is the Leaves module. The results of this research are the use of several features in the Odoo software, including creating types of leave, granting leave rights, submitting leave, providing leave submission results, viewing the results of leave submissions. This research is expected to facilitate the management of leave, especially filing and recording leave history so that it is systemized so that the quality of human resource management is preferable.